Arnold Wesker - Leeming, Glenda (Writers and Their Work Series., 1972)
Arnold Wesker belongs to the generation of dramatists who grew up in the 1940s and whose dissatisfaction with the status quo revolutionized the British theatre in the late 1950s. Both in his plays and his other activities, Wesker has shown a more explicit commitment than his fellow dramatists to left-wing political ideals. In the 1960s he was associated with the Committee of One Hundred in its protests against nuclear weapons, and he directed Centre Fortytwo,